Development of a kinetic model structure for simultaneous saccharification and fermentation in rice wine production. Issue 4 (16th September 2015) - Liu, Dengfeng; Zhang, Hongtao; Xu, Baoguo; Tan, Jinglu
<x xml:space="preserve">Abstract</x> Rice wine experiments were performed with glutinous rice, Chinese wheat Qu, and the yeast strain Saccharomyces cerevisiae Su‐25 at ambient temperature or at different set temperatures. The major products were identified and measured by HPLC. A low‐order kinetic model structure (form or construct of model with adjustable parameters) was proposed for the major products and the main reactions of the simultaneous saccharification and fermentation (SSF) process. The model structure was then tested for its ability to capture the main kinetic variations after parameter optimization by a least‐squares algorithm. The proposed model structure was found useful in describing the measured kinetic variations except those in maltotriose production under ambient conditions. The estimated reaction rates correctly reflected the variations known or observed from the experiments, and provided insights into the reaction processes in terms of reaction speeds, dominant variations and primary products. While additional research is warranted for further validation and refinement, the proposed model structure shows promise for describing the SSF process of rice wine. Copyright © 2015 The Institute of Brewing & Distilling